PERAN PARTAI GOLONGAN KARYA DALAM MENINGKATKAN PARTISIPASI PEMILIH PERSPEKTIF SIYASAH DUSTURIYAH - Miftah, Muhammad Ariel; Sastrawati, Nila; Anis, Muhammad (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2023)
This study examines the extent of the role of the Working Group Party in increasing community political participation in Bone Regency in the perspective of siyasah syar’iyyah with juridical and normative syar’i approaches. Various efforts have been made by the Working Group Party in increasing people’s political participation, such as building good political communication, encouraging the people of Bone to participate in every election momentum. Obstacles that affect the increase in political participation of the community in Bone Regency include the minimal cost of political parties, public apathy towards political activities, and political education to the community that has not been maximally pursued by various stakeholders. In Siyasah Dusturiyah’s view, community involvement in government, including those carried out by political parties, is part of the application of the principle of deliberation.